Improving Knowledge and Creativity of Students UPTD SD Negeri 13 Sosopan KKN 158 UINSU - Rahman, Benni Ichsanda; Siregar, Putri Aisyah; Jannah, Raudhatul; Rizki, Puput Fadhilah (Edumaspul: Jurnal Pendidikan, 2022)
Creativity is part of the characteristics of human courage that echoes who he is and what humans become in the future. In every act of creativity, individuals will feel a good relationship between themselves and others. This study aims to determine the development of creativity of students in UPTD SD Negeri 13 Sosopan. This research is a research with phenomenology research method because in this journal there is a lot of income and studying various disclosures of phenomena that occur and are experienced by many individuals so that it can produce various conscious life experiences. The results showed that KKN 158 student service activities took the initiative to help teaching activities at UPTD SD 13 Sosopan, Sosopan Village to increase students' knowledge and creativity. The conclusion obtained is that it is very important for us to develop creativity and knowledge for students. So that students can be more active in working with various kinds of knowledge they have.